Application Of Gamification Method In SKI Learning At MTS Al-Fathimiyah To Increase Learning Interest - Ratna, Dewi; Meila, Nadiya; Ruhyana, Destia; Farida, Nur Aini (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Education is a humanistic process that aims to humanize humans through respect for the basic rights of every individual, including students as the next generation. In the learning process, students' interest in learning is an important factor that influences the achievement of educational goals. Low interest in learning, as found in class VII MTs Al-Fathimiyah in the subject of Islamic Cultural History (SKI), can be caused by the use of monotonous learning methods, such as lectures. This study aims to increase students' interest in learning through the application of the gamification method, an innovative approach that adopts game elements to create a fun and interactive learning experience. The study used the Classroom Action Research (CAR) method, Kemmis and McTaggart model in two cycles, involving SKI teachers and male class VII students as the main subjects. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. The results of this study in cycle 1 achieved 52.9% and cycle 2 achieved 88.2%. Thus, it can be concluded that the gamification method can increase students' interest in learning Islamic Cultural History.